Pengaruh Metode Pembelajaran Berbasis Gamifikasi Terhadap Motivasi Belajar Siswa di Kota Tomohon - Siregar, Dina Mariana; Febrianto, Rachman; Paparang, Hessel Zakharia (Flourishing Journal, 2025)
Rapid development of digitalization in education necessitates the implementation of innovative learning strategies that can enhance students’ active engagement and support the achievement of optimal learning outcomes. One approach considered relevant in this context is gamification-based learning, which is designed to create a more interactive, engaging, and motivating learning environment. This study aims to empirically examine the effect of gamification learning methods on the learning motivation of senior high school students in Tomohon City. The study employed a quantitative approach with a correlational survey design and simple regression analysis. The research population consisted of senior high school students in Tomohon City, with a sample of 169 respondents. The research instruments included Likert-scale questionnaires measuring learning motivation and gamification-based learning, with response options ranging from 1 to 5. Data analysis was conducted using SPSS version 24. The results indicate that gamification-based learning methods influence students’ learning motivation. The Kolmogorov–Smirnov normality test showed p = .02 (< 0.05), while the R² value of 0.091 indicates that gamification accounts for 9.1% of the variance in learning motivation. These findings suggest that gamification has the potential to serve as an alternative learning strategy in the digital era, although further development is needed to achieve greater effectiveness. AbstrakPerkembangan digitalisasi pendidikan menuntut penerapan strategi pembelajaran inovatif yang mampu meningkatkan keterlibatan aktif siswa serta mendukung pencapaian hasil belajar yang optimal. Salah satu pendekatan yang dinilai relevan dalam konteks tersebut adalah pembelajaran berbasis gamifikasi, yang dirancang untuk menciptakan suasana belajar yang lebih interaktif, menarik, dan memotivasi. Penelitian ini bertujuan untuk menguji secara empirik pengaruh metode pembelajaran gamifikasi terhadap motivasi belajar siswa SMA di Kota Tomohon. Penelitian menggunakan pendekatan kuantitatif dengan desain survey korelasional dan teknik analisis regresi sederhana. Populasi penelitian mencakup siswa SMA di Kota Tomohon, dengan sampel sebanyak 169 responden. Instrumen penelitian berupa skala Likert motivasi belajar dan pembelajaran gamifikasi dengan rentang skor 1–5. Analisis data dilakukan menggunakan aplikasi SPSS versi 24. Hasil penelitian menunjukkan bahwa metode pembelajaran gamifikasi berpengaruh terhadap motivasi belajar siswa. Uji normalitas Kolmogorov–Smirnov menunjukkan nilai p = .02 (< 0,05), sedangkan nilai R² sebesar 0,091 mengindikasikan bahwa gamifikasi berkontribusi sebesar 9,1% terhadap variasi motivasi belajar siswa. Temuan ini menunjukkan bahwa gamifikasi berpotensi menjadi alternatif strategi pembelajaran di era digital, meskipun masih memerlukan pengembangan lebih lanjut untuk meningkatkan efektivitasnya.